Isolation of Lactic Acid Bacteria from Malaysian Non-Broiler Chicken (Gallus gallus) Intestine with Potential Probiotic for Broiler Feeding - Tengku Abdul Hamid, Tengku Haziyamin; Ezani,; Ezureen (IIUM Engineering Journal, 2011)
Probiotic supplement can function as substitute for antibiotics especially in the broiler chicken feeding which can form an integral part of organic farming. Broiler forms one of an important protein source in South East Asia. Lactic acid bacteria (LAB) are important inhabitants of animal intestine and are useful source of probiotic microorganisms. Non-broiler chicken could be an ideal source of probiotic microorganisms that can be utilized for large scale broiler feeding. Our studies have successfully identified, through morphological and biochemical tests, 11 LAB isolates from gastrointestinal tract of local non-broiler chicken (Gallus gallus). These isolates have the ability to utilize lactose as part of their metabolism process and all showed negative reactions on catalase test. Out of the eleven (11) isolates, three (3) isolates were Gram-positive cocci and remaining isolates were of Gram-positive bacilli. Three isolates (E4, E11 and E17) showed at least 10 mm inhibitory effects on disc diffusion test against pathogenic bacteria Salmonella typhimurium. The partial 16S rRNA gene sequencing showed that one isolate (E17) has 89% similarity with Lactobacillus rhamnosus. These LAB strains isolated from Malaysian domestic non-broiler chicken gastrointestinal tract can potentially be used as a component for probiotics formulation in poultry feeding. ABSTRAK: Makanan tambahan probiotik boleh berfungsi sebagai pengganti antibiotik terutamanya dalam pemakanan ayam pedaging yang akan membentuk bahagian kamiran dalam penternakan organik. Ayam pedaging merupakan sumber protein penting di Asia Tenggara. Bakteria asid laktik (lactic acid bacteria (LAB)) merupakan penghuni penting dalam usus haiwan dan merupakan sumber penting dalam mikroorganisma probiotik. Ayam bukan pedaging sesuai dijadikan sumber mikroorganisma probiotik agar dapat digunakan sebagai pemakanan ayam pedaging secara besar-besaran. Kajian telah berjaya mengenal pasti, melalui kaedah morfologi dan uji kaji biokimia, 11 LAB diasingkan daripada salur gastrousus ayam bukan pedaging (Gallus gallus). Pencilan ini berupaya menggunakan laktosa sebagai sebahagian daripada proses metabolisma dan semuanya menunjukkan kesan negatif terhadap ujian katalase. Daripada sebelas (11) pencilan, tiga (3) pencilan adalah kokus gram-positif dan pencilan yang lainnya adalah basilus gram-positif. Tiga pencilan (E4, E11 dan E17) menunjukkan sekurang-kurangnya 10 mm kesan rencatan terhadap ujian resapan cakera terhadap bakteria patogen Salmonella typhimurium. Sebahagian daripada urutan gen 16S rRHA menunjukkan bahawa satu pencilan (E17) mempunyai 89% persamaan dengan Lactobacillus rhamnosus. Strain LAB ini diasingkan daripada salur gastrousus ayam tempatan bukan pedaging, sesuai digunakan sebagai komponen untuk rumusan probiotik dalam pemakanan ayam-itik.